Oral rehabilitation in a patient with odontophobia – Case report - Brazão, Carla do Socorro Jatahy; Gauch, Lurdete Maria Rocha; Esteves, Renata Antunes; Gauch, Isabelle Rocha; Pereira, Tasso César da Costa; Dias, Hercules Bezerra; Corrêa, Davi Lavareda; Corrêa, Vania Castro; Corrêa , Suelen Castro Lavareda; Uchôa , Sue Ann Lavareda Corrêa; Pedrosa, João Pedro Costa; Pedrosa, Simone Soares (Seven Editora, 2024)
Despite technological advances in dentistry, negative feelings still prevail in the area, such as odontophobia, which the World Health Organization classifies into three stages. Patients with this condition often postpone treatments, cooperate little, and resort to palliative medications, compromising their oral health. This study reports the case of a patient who faced oral complications due to odontophobia, highlighting the rehabilitation treatment plan adopted, its phases and results obtained. The diagnosis of anxiety was made using the Dental Anxiety Scale (DAS), created by Corah in 1969. It is concluded that understanding the patient's general conditions and motivation to seek dental treatment is crucial for a proper diagnosis and to establish an effective treatment plan. The installation of the prostheses resulted in a significant improvement in the patient's self-esteem, social well-being, reduced anxiety and improvements in diet. DOI:https://doi.org/10.56238/sevened2024.014-002